2015
DOI: 10.5296/jab.v3i1.6738
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase Induction in Three Aspergillus Species Isolated From Artemisia annua L. Plantation Soil Using Different Cellulose Substrates

Abstract: This stu annua cellulas within t was car powder species, recorde ability a were se was ana CMCas Carboxy highest 0.045IU high en media r the 3 rd d perform

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Glucose units one of the smaller sugar components produce by cellulases are a group of hydrolytic enzymes capable of hydrolysing cellulose. The nature's biodegradation processes product by cellulolytic enzymes where plant lignocellulosic materials are efficiently degraded by cellulolytic fungi [24]. This result agreed with the study [25] regardingan Training to isolate the fungi from the undiscovered soils of (Western Ghats) and screen them for the production hydrolytic enzymes as cellulase and CMCase.…”
Section: Screening Of Fungal Isolates For Cellulytic Activitysupporting
confidence: 82%
“…Glucose units one of the smaller sugar components produce by cellulases are a group of hydrolytic enzymes capable of hydrolysing cellulose. The nature's biodegradation processes product by cellulolytic enzymes where plant lignocellulosic materials are efficiently degraded by cellulolytic fungi [24]. This result agreed with the study [25] regardingan Training to isolate the fungi from the undiscovered soils of (Western Ghats) and screen them for the production hydrolytic enzymes as cellulase and CMCase.…”
Section: Screening Of Fungal Isolates For Cellulytic Activitysupporting
confidence: 82%
“…Based on morphological and cultural characteristics, RPW 1/3 and RPW 1/10, RPW 1/6 and RPW 1/9, and RZWM 3/1 were identified as Aspergillus flavus, Aspergillus terreus and Aspergillus niger, respectively. Many Species of Aspergilli produces cellulases and exhibits strong hydrolytic activity towards cellulose (Ogbonna et al 2015). Some species of Aspergilli like A. flavus (Saritha and Maruthi 2010), A. niger (Chinedu et al 2008) and A. terreus (Jahromi et al 2011) were found effective in the biodegradation of different lignocellulosic materials by producing oxidative and hydrolytic enzymes.…”
Section: Lignocellulolytic Activity In Solid State Fermentationmentioning
confidence: 99%